Strategies for the control of malolactic fermentation : characterisation of Pediocin PD-1 and the gene for the malolactic enzyme from Pediococcus damnosus NCFB 1832 - Bauer, Rolene (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD Agric)--University of Stellenbosch, 2004.